Exploring the gut microbiome in combat sports: a systematic scoping review - Carlone, J.; Rossi, C.; Bianco, A.; Drid, P.; Parisi, A.; Fasano, A. (Sports, 2026)
The gut microbiota represents a complex microbial ecosystem with the potential to influence athletic performance, energy metabolism, inflammatory responses, and recovery capacity in athletes. However, the specific relationship between microbiota and performance in combat sport athletes remains poorly characterized. This scoping review systematically maps current evidence on gut microbiota-combat sports performance relationships, identifies microbial response patterns to training and competition, evaluates nutritional prebiotic and probiotic interventions, and highlights methodological gaps to guide future research. Following the PRISMA-ScR framework, 8 studies were identified, which included 247 elite and high-level athletes, comprising 169 males and 78 females, with sample sizes ranging from 12 to 53 across wrestling, mixed martial arts, martial arts, judo, and taekwondo. Associations were observed between gut microbiota characteristics and training intensity, competition level, weight management, and pre-competition psychological states. Limited taxonomic consistency was observed across studies, with most bacterial genera appearing in a single investigation, precluding the identification of robust sport-specific microbial signatures. Preliminary trials demonstrated improvements in gastrointestinal symptoms, aerobic performance, and psychological fatigue with prebiotic and probiotic interventions. However, small sample sizes and methodological heterogeneity across studies limit generalizability and preclude definitive conclusions regarding the role of gut microbiome in combat sports performance.